2001
DOI: 10.1093/gerona/56.suppl_1.20
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction Mimetics: Metabolic Interventions

Abstract: Caloric restriction (CR) retards diseases and aging in laboratory rodents and is now being tested in nonhuman primates. One way to apply these findings to human health is to identify and test agents that may mimic critical actions of CR. Panel 2 focused on two outcomes of CR, reduction of oxidative stress and improved glucoregulation, for which candidate metabolic mimics exist. It was recommended that studies on oxidative stress should emphasize mitochondrial function and to test the efficacy of nitrone and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 123 publications
3
76
0
1
Order By: Relevance
“…50 In contrast to 0.2% glucose, which induced the Gad8-S546 phosphorylation in glucosestarved cells, the same concentration of 2-DG failed to recover the Gad8 phosphorylation at all (Fig. 2D).…”
Section: Torc2 Remains Active During Nitrogen Starvationmentioning
confidence: 85%
“…50 In contrast to 0.2% glucose, which induced the Gad8-S546 phosphorylation in glucosestarved cells, the same concentration of 2-DG failed to recover the Gad8 phosphorylation at all (Fig. 2D).…”
Section: Torc2 Remains Active During Nitrogen Starvationmentioning
confidence: 85%
“…Upon transport into the cells, 2-DG is phosphorylated by hexokinase to 2-DG-P. However, unlike G-6-P, 2-DG-P cannot be further metabolized by phosphohexose isomerase, which converts G-6-P to fructose-6-phosphate (Weindruch et al, 2001). 2-Deoxyglucose-P is trapped and accumulated in the cells, leading to inhibition of glycolysis mainly at the step of phosphorylation of glucose by hexokinase.…”
Section: -Deoxyglucosementioning
confidence: 99%
“…However, unlike glucose-PO4, the 2-DG-PO4 cannot further be metabolized by the GPI. In addition, 2-DG could inhibit GPI (47), and then down-regulate its downstream glycolysis-related genes. Consistent with results from the glycolytic pathway regulated by 2-DG, our data revealed that the upstream genes of GLUT1 and HK1 are overexpressed subsequent to 2-DG administration, and the downstream genes of GPI, GAPD, PGK1, PGK2, ENO2 and PKM2 are underexpressed in CRC cell lines.…”
Section: -------------------------------------------------mentioning
confidence: 99%